2012
DOI: 10.1161/strokeaha.111.645507
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Future for Endovascular Treatment of Intracranial Atherosclerotic Disease After Stenting and Aggressive Medical Management for Preventing Recurrent Stroke and Intracranial Stenosis (SAMMPRIS)?

Abstract: The Stenting and Aggressive Medical Management for Preventing Recurrent Stroke and Intracranial Stenosis (SAMMPRIS) trial, a randomized clinical trial comparing aggressive medical management to stenting with aggressive medical management for symptomatic intracranial stenosis, was prematurely halted when a high rate of periprocedural events was found in the stent arm. The trial also demonstrated a high rate of stroke with medical management. This article explores possible reasons for these outcomes and discusse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 38 publications
0
20
0
1
Order By: Relevance
“…4 In light of the disappointing results 5 of the Stenting versus Aggressive Medical Management for Preventing Recurrent Stroke in Intracranial Arterial Stenosis (SAMMPRIS) trial, we are reminded that lesion morphology of the intracranial artery may also be a prominent factor that influences the rate of periprocedural complications. 6,7 Knowledge of the wall characteristics of the MCA may be useful in interpreting the data of the SAMMPRIS trial, selecting patients for percutaneous transluminal angioplasty and stenting (PTAS), and designing individualized operating plans. High-resolution MR imaging has been increasingly used in recent years to identify the wall features of the intracranial artery.…”
mentioning
confidence: 99%
“…4 In light of the disappointing results 5 of the Stenting versus Aggressive Medical Management for Preventing Recurrent Stroke in Intracranial Arterial Stenosis (SAMMPRIS) trial, we are reminded that lesion morphology of the intracranial artery may also be a prominent factor that influences the rate of periprocedural complications. 6,7 Knowledge of the wall characteristics of the MCA may be useful in interpreting the data of the SAMMPRIS trial, selecting patients for percutaneous transluminal angioplasty and stenting (PTAS), and designing individualized operating plans. High-resolution MR imaging has been increasingly used in recent years to identify the wall features of the intracranial artery.…”
mentioning
confidence: 99%
“…Wingspan was reported to be safe and may contribute to favorable outcomes [21], however, the SAMMPRIS trial indicated that intracranial stenting might increase periprocedural stroke and death rate in comparison to aggressive medical treatment. Operators with greater experience could decrease stroke and death rates in stented patients, and the SAMMPRIS trial was limited by a single technique and device system [22]. Therefore, the results of the prematurely terminated SAMMPRIS study support modification but not discontinuation of our approach to intracranial angioplasty and/or stent placement for intracranial stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…6,7,32,33 Device manufacturers and scientists will have to reevaluate stent design and develop new products with superior safety and efficacy profiles. Many have called for different materials to be used and suggested potential drug-eluting models that have thus far been used with varying success worldwide.…”
Section: Intracranial Stenting and Balloon Angioplastymentioning
confidence: 99%
“…[4][5][6][7][8] While dual antiplatelet therapy has been a mainstay of treatment for symptomatic patients, the use of balloon angioplasty with or without stent placement has undergone a recent paradigm shift-mainly in light of data from the Stenting versus Aggressive Medical Management for Preventing Recurrent Stroke in Intracranial Stenosis (SAMMPRIS). 9 This study is the only prospective randomized trial regarding the use of balloon angioplasty and stenting as treatment of ICAD.…”
Section: Introductionmentioning
confidence: 99%